Effects of trace Si impurities in water on the growth of calcite nanoparticles. Issue 4 (22nd December 2021) - Kezuka, Yuki; Murata, Hidenobu; Yoshida, Maya; Eguchi, Kenichiro; Nakahira, Atsushi; Tajika, Masahiko
Abstract : Si impurities act as proton buffers in water and prevent the formation of the alkaline environment required for calcite growth. Abstract : Effects of trace inorganic Si impurities in water on the growth of calcite nanocrystals are evaluated using high-purity Ca(OH)2 and amorphous SiO2 as the starting materials. First, pristine calcite spheroidal particles (∼40 nm) are synthesized by CO2 bubbling into Ca(OH)2 aqueous slurry. Next, slurries of calcite particles with several different Si-coexisting concentrations were prepared and incubated at 95 °C to induce the calcite growth. Particle morphology before and after the slurry incubation were investigated, and growth inhibition with increasing Si concentrations was clearly observed. Amorphous SiO2, which is hydrolysed into orthosilicic acid (Si(OH)4 ) in water at elevated temperatures, is found to act as a proton buffer, and prevent the formation of the alkaline environment required for calcite growth. Si-coexisting effects demonstrated in this study are important for understanding the calcite mineralization process and particle morphology control.